Installation of borehole strainmeters to monitor North Anatolian fault near Istanbul - Bal, Osman. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2018., 2018)
The North Anatolian Fault Zone (NAFZ) , which forms the plate boundary between the Anatolian plate in the south and the Eurasian plate in the north, runs under the Marmara Sea and is located less than 20 km from the city of _Istanbul. According to historical seismicity data and recurrence times; an earthquake, which is bigger than magnitude 7, is expected. Geodesists have been doing many observations on the NAFZ with various techniques since 1972. Geodesy Department of Kandilli Observatory and Earthquake Research Institute (KOERI) plays a crucial role on deformation measurement on the NAFZ with its micro-geodetic networks since 1989. By using the developing technology in time, Geodesy Department of KOERI incorporated some other terrestrial deformation measuring techniques like creepmeters and strainmeters. The aim of this thesis is to discuss, the need of the strainmeter, installation cases for two boreholes, solutions found for site speci c problems and the result of installation. Installed strainmeters will allow us to monitor potential slow-slip events along the Marmara Seismic Gap.
Keywords: North Anatolian Fault Zone (Turkey); Faults(Geology) -- Turkey.; Seismic tomography.